Evaluating the Effectiveness of 5c-Based Risk Mitigation and Sharia-Compliant Restructuring in Reducing NPF in Sharia Mortgage Financing: A Case Study of Bank BTN Syariah Diponegoro Surabaya - Rifantini, Adinda; Ardyansyah, Farid (Universitas Nurul Jadid, 2025)
This study analyzes the implementation and effectiveness of risk mitigation strategies in Sharia Home Ownership Loan (KPR) financing using the 5C principles (Character, Capacity, Capital, Collateral, Condition) and sharia-compliant restructuring mechanisms to reduce Non-Performing Financing (NPF) at Bank BTN Syariah Diponegoro Surabaya. The issue is critical because the national NPF ratio for sharia mortgages has shown fluctuations in recent years, posing threats to portfolio quality and institutional stability. Using a descriptive qualitative approach, data were collected through semi-structured interviews with three key informants directly involved in consumer financing analysis, collection, and documentation, complemented by secondary data from internal bank reports and regulatory sources. Data validity was ensured through source triangulation, technical triangulation, and member checking. The findings show that the rigorous application of the 5C principles helped prevent high-risk applicants from entering the financing portfolio, with 23% of applications rejected during 2024–2025 due to 5C deficiencies. Meanwhile, restructuring measures—through rescheduling, reconditioning, and contract adjustments—helped stabilize debtor repayment abilities and contributed to a decline in potential NPF escalation. Internal branch records indicate that these combined mitigation strategies helped maintain NPF at a controlled level despite wider national fluctuations. This study contributes to the literature by integrating pre-disbursement (5C) and post-disbursement (restructuring) mitigation frameworks within sharia mortgage financing, addressing a gap in existing studies that often examine these mechanisms separately. Practically, the results provide guidance for Islamic banks in strengthening responsive and sharia-compliant risk management systems.